Cultural competence of undergraduate student nurses: a multicenter study - Lucía Sagarra-Romero; Enrique Ramón-Arbués; Isabel Huércanos-Esparza; Indrani Kalkan; Nuran Kömürcü; Valérie Vanceulebroeck; Shana Dehaes; Margarida Coelho; Antonio Casa-Nova; Isabel Antón-Solanas (Universidade de São Paulo, 2024)
Objective: to evaluate the level of cultural competence of an undergraduate nursing students' population from four European higher education institutions. Method: a total of 168 nursing students from four different countries were included in our study. The study methodology involved a cross-sectional assessment of cultural competence among undergraduate nursing students from four European universities. Data collection included sociodemographic variables, as well as the following validated tools: the Intercultural Sensitivity Scale, the Cultural Competence Assessment Tool (student version) and the Cultural Awareness Scale. Results: our results indicated that students demonstrated a high level of intercultural sensitivity but a moderate level of cultural competence and cultural awareness. Variations existed among students from different countries, suggesting potential differences in educational approaches. Despite expectations that higher-level students would exhibit greater cultural competence, no significant differences were found by year of study, indicating a lack of effective integration of cultural competence into nursing curricula. Conclusion: nurse educators should consider the students' cultural competence before designing related study programmes. Training programmes related to cultural competence should include elements which have been associated with enhanced cultural competence, including language skills, cultural encounter, and opportunities for internationalisation.